SPE Annual Technical Conference and Exhibition 2005
DOI: 10.2118/95515-ms
|View full text |Cite
|
Sign up to set email alerts
|

Asphaltene-Induced Formation Damage: Effect of Asphaltene Particle Size and Core Permeability

Abstract: Phase behaviour results indicated that the mass and size of asphaltene particles precipitated from the mixtures were strongly dependent on the CO 2 concentration. Coreflood test results showed that the severity of formation damage was related to the initial core permeability as well as the quantity and size of the asphaltene particles precipitated. The damage mechanism was found analogous to the 1/3 and 1/7 rule of thumb that related the size of particulates in injected water to potential permeability reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 7 publications
0
37
0
Order By: Relevance
“…To facilitate comparison, the third set of experiment was carried out under the same procedures of EXP-2, with the exception that the injecting CO 2 in this case was the carbon dioxide stream saturated with nanoparticles as opposed to the pure CO 2 case. Polydimethylsiloxane (PDMS) was used for dispersing nickel oxide nanoparticles into CO 2 , as suggested in the literature (Shah and Rusheet 2009).…”
Section: Methodsmentioning
confidence: 99%
“…To facilitate comparison, the third set of experiment was carried out under the same procedures of EXP-2, with the exception that the injecting CO 2 in this case was the carbon dioxide stream saturated with nanoparticles as opposed to the pure CO 2 case. Polydimethylsiloxane (PDMS) was used for dispersing nickel oxide nanoparticles into CO 2 , as suggested in the literature (Shah and Rusheet 2009).…”
Section: Methodsmentioning
confidence: 99%
“…Asphaltene caused permeability reduction in conventional reservoirs has been well studied. Experimental work showed permeability reduction caused by asphaltene deposition in conventional reservoir cores, and effects of factors on permeability reduction were investigated . It was found that the injection gas concentration has the most impacts on permeability reduction.…”
Section: Introductionmentioning
confidence: 99%
“…The process of accurately describing asphaltene behavior may begin at that stage. To date, tremendous efforts have been made to describe the phenomena of asphaltene precipitation (Strivastava et al, 1999;Kocabas et al, 2000;Takahashi et al, 2003;Sim et al, 2005;Papadimitriou et al, 2007). Several mathematical models have been proposed for the prediction of the rate of deposition and asphaltene solubility.…”
Section: Introductionmentioning
confidence: 99%